Dynamic Performance Evaluation of Concrete Building Using Low-Yield Point Steel Shear Panels - Nima Marzban; Parisa Esmaeiltabar Nesheli (Shock and Vibration)
Steel shear walls are a novel component in the field of construction. It has been of special interest to structural engineers for the reinforcement of steel buildings for the recent decades. Its unique features have attracted more attention, and its features are economical, easy to implement, light weight compared to similar systems, high ductility, fast installation, high energy absorption, and a significant reduction in residual stress in the structure. All the reasons made researchers think about studying its use in the repair of concrete buildings. Because this system has a low weight, it does not add extra load to the structure, and even with its connections, it strengthens the beams and columns around it. The design of this system in concrete buildings does not seem to be economical except in the case of restoration. In this paper, preliminary explanations of the steel shear wall are presented for more familiarity, and in the following sections, the study of reinforcement and repair of concrete structures will be studied and its difference with the low-yield point will be considered. Finally, the test results will be reviewed. The results of this study show that LYP steel shear panels cause a lot of energy loss and absorption, which is very useful in the safety of buildings exposed to severe earthquakes.